EEDF MEASUREMENTS AND EXCITATION PROCESSES IN THE VICINITY OF A HELIUM DISCHARGE CONSTRICTION (Journal of Sciences, Islamic Republic of Iran)
Axial distributions of plasma and floating potentials, electron number density and the electron energy distribution function (EEDF) have been measured in the double layer (DL) region of an He discharge constriction. Excitation processes in the constriction region are studied. Using a linearization method for the nonstationary balance equations and choosing appropriate discharge conditions, the step excitation rate by electron impact for the 2 S 3 D transition in He is determined